MINAT DAN HASIL BELAJAR SISWA MELALUI PENDEKATAN KETERAMPILAN PROSES SAINS DAN MEDIA GAMBAR - Uswatun Hasanah; Singgih Bektiarso; Sudarti (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the effect of the science process skills approach and picture media on the interest and learning outcomes of physics class XI students at SMAN 1 Gambiran. This type of research is quantitative with a confirmatory causal research design. The number of samples used was 160 respondents from all XI MIPA classes. Data collection techniques through interviews, documentation and questionnaires. Data analysis used descriptive analysis techniques and SEM analysis. Based on the research results, it is known that the science process skills approach affects interest in learning, science process skills affect learning outcomes with a significant level of 10%, Picture media has an effect on interest and learning outcomes. So from this research it is hoped that teachers can apply and improve science process skills and picture media to increase student interest and learning outcomes